Irish writers and the thirties : art, exile and war - Goldstone, Katrina, 1958- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This original study focusing on four Irish writers - Leslie Daiken, Charles Donnelly, Ewart Milne and Michael Sayers - retrieves a hitherto neglected episode of Thirties literary history which highlights the local and global aspects of Popular Front cultural movements. From interwar London, to the Spanish Civil War and the USSR, the book examines the lives and work of Irish writers through their writings, their witness texts and their political activism. The relationships of these writers to George Orwell, Samuel Beckett, T.S. Eliot, Nancy Cunard, Williams Carlos Williams, and other figures of cultural significance within the interwar period, sheds new light on the internationalist aspects of a leftist cultural history. The book also explores how Irish literary women on the Left defied marginalization. The impetus of the book is not merely to perform an act of literary salvage but to find new ways of re-imagining what might be said to constitute Irish literature mid-20th century; and to illustrate how Irish writers played a role in a transforming political moment of the 20th century. It will be of interest to scholars and students of cultural history and literature, Irish diaspora studies, Jewish studies, and the social and literary history of the Thirties"--
Art and exile, 1936-1939. "Dublin to Euston our via dolorosa..." -- "Life was one long continuum of agitprop" -- "Equality has ceased to be accorded to us, save on paper" -- "Visit Leningrad and take off your hat" -- Art and war, 1936-1945. "I too have heard companion voices die" -- "Now when all the buildings of Europe don their sackcloth..." -- Epilogue: Aftermath of the thirties epitaphs and legacies ; "...And on my grave, I see no flowers from any people".
OCLC-licensed vendor bibliographic record.
Keywords: Daiken, Leslie -- Political and social views; Donnelly, Charles Patrick, -- 1914-1937 -- Political and social views; Milne, Ewart, -- 1903-1987 -- Political and social views; Sayers, Michael, -- 1911-2010 -- Political and social views; English literature -- Irish authors -- History and criticism; English literature -- 20th century -- History and criticism; Fascism and literature; HISTORY / Europe / Ireland; HISTORY / Modern / 20th Century; HISTORY / Social History